Management of transient ischaemic attacks in the emergency department: a quality improvement project. Issue 1 (17th November 2014) - Wydall, Simon; Gordon, Andrew; Sims, Mark
Abstract: The initial management of transient ischaemic attacks (TIAs) effectively triages patients into either high or low risk categories. The literature demonstrates that the identification of high risk patients significantly reduces the subsequent risk of stroke. The administration of aspirin following a TIA reduces the risk of stroke by approximately 25%. A full cycle retrospective audit which included a baseline audit with two improvement cycles was completed. The notes of every patient presenting to Croydon University Hospital's emergency department (ED), who were subsequently diagnosed with a TIA were reviewed, with the aim of identifying areas for improvement and to implement sustainable long term interventions aimed to improve patient safety. The patient's notes were compared with the guidelines for the management of TIA. The baseline audit demonstrated results requiring an immediate intervention. A teaching session was provided for new FY2 doctors starting their emergency medicine rotations, which covered the initial management of TIA and the importance of following the local guideline. The first improvement cycle saw an improvement in all outcomes measured. A statistically significant improvement (P-value = 0.05) was seen in the documentation of symptoms in the prior week and the prescription of antiplatelets in the department. Furthermore, where only 31% of TIA patients received antiplatelets at the baseline measurement, 86% received this treatment during the first improvement cycle. This means that 55% more patients received improved initial management, subsequently reducing their stroke risk by 25%. Similar results were seen in the second improvement cycle, thus demonstrating the intervention had been both successful and sustainable. In conclusion, a simple intervention can provide significant and sustainable improvements to the management of TIA in the ED.